D2 region of the 28S RNA gene: A too-conserved fragment for inferences on phylogeny of South American triatomines - Guerra, Ana Letícia [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP]; Banho, Cecília Artico [UNESP]; De Oliveira, Jader [UNESP]; Da Rosa, João Aristeu [UNESP]; De Azeredo-Oliveira, Maria Tercília Vilela [UNESP] (American Society of Tropical Medicine and Hygiene, 2016)
The brasiliensis complex is composed of five triatomine species, and different approaches suggest that Triatoma lenti and Triatoma petrochiae may be the new members. Therefore, this study sought to analyze the phylogenetic relationships within this complex by means of the D2 region of the 28S RNA gene, and to analyze the degree of polymorphism and phylogenetic significance of this gene for South American triatomines. Phylogenetic analysis by using sequence fragments of the D2 domain did not allow to perform phylogenetic inferences on species within the brasiliensis complex, because the gene alignment composed of a matrix with 37 specimens exhibited only two variable sites along the 567 base pairs used. Furthermore, if all South American species are included, only four variable sites were detected, reflecting the high degree of gene conservation. Therefore, we do not recommend the use of this gene for phylogenetic reconstruction for this group of Chagas disease vectors.